Awareness of Oral Complications and Oral Hygiene Habits of Subjects with Diagnosed Diabetes Mellitus - Çankaya Hülya; Güneri Pelin; Epstein Joel B.; Boyacıoğlu Hayal (Balkan Stomatological Society, 2018)
Background/Aim: The aim was to evaluate Diabetes Mellitus (DM) patients' awareness of their risk for oral and dental complications, to evaluate their oral health behaviors, assess their sources of related information, and to detect the influence of their awareness on oral health and dental management.